A escola como espaço de convivência: a prevenção e a redução do bulismo escolar - Munarin, José Carlos (2007)
In the present study, we investigated the phenomenon of violence, implicit in the relationships among students, as one of the factors that interfere significantly in the social, emotional and intellectual development of children and students. The purposes of this study were to characterize the pedagogic and normative instruments of a public school of the School Superintendence of Birigui SP and to identify the strategies and educational practices of intervention used by managers and teachers in the prevention and reduction of the school bullying. Based on approach of qualitative research, a study of case of instrumental character was accomplished. For the data collection, were analyzed three documents of the School - the Management Plan, the Pedagogical Proposal and the Code of Norms and made semi-structured individual interviews with Managers and teachers. The data were analyzed, classified and presented with the purpose of making evident the intentions and practices used by managers and teachers, based on the pedagogic and normative documents that sustain it. We verified that the managers recognize the phenomenon of bullying in the school context and have used intervention practices to face this violence problem, but they also need to guide the teachers in its prevention and reduction. The teachers possess specific knowledge about this form of violence. They also recognize the bullying as aggressive practice that needs intervention. They try to intervene to overcome it, but need pedagogic and extra-school support to be more effective in this action. The utilized strategies are based on the students' awareness in relation to their transgressive conduct and in the immediate intervention in the conflicts among students. However some teachers feel difficulty in working with situations of more complex bullying. From this study, it is possible to conclude that it is necessary an articulate work between the management team and the teachers for preventing and reducing the bullying in the school context. In addition, it can still be stated that the intervention of the adult-educators is an essential condition for overcoming the school bullying.